ANALISIS SEKTOR UNGGULAN KABUPATEN SLEMAN TAHUN 2006 – 2011 - Veny Anindya Puspitasari (Universitas Bunda Mulia, 2017)
Sleman Regency is one regency in Province Yogyakarta Special Region that has the potential as a contributor for Yogyakarta Regional Gross Domestic Bruto and Indonesia Gross Domestic Product. This descriptive quantitative paper will discuss about what the base sectors in Sleman Regency so that worthy to be developed. Location quotation (LQ) method was used to calculate and explain the base sectors in Sleman Regency. The resultas obtained that base sectors in Sleman in 2010 and 2011 were processing industry, electricity, gas, and clean water, construction, trade, hotel, and restaurants, and financial sectors was the impact of Merapi eruption last year that causes huge material losses.Key Words- Economy Potential, Base Sector, Location Quotation, Sleman Regency